Divorce and Remarriage in Norway: A Prospective Cohort Study Between 1981 and 2013. Issue 8 (17th November 2019) - Zahl-Olsen, Rune; Thuen, Frode; Espehaug, Birgitte
ABSTRACT: As the population of divorced adults has increased, the number of remarriages has followed. Previous research has mainly compared first-time marriages with remarriages, whereas this study analyzes 4 different constellations of marriages: first time for both spouses, first time for one and second time for the other, second time for both, and third time or more for at least one member of the couple. The analyses are based on data from all Norwegian 2-sex marriages formed from 1981 to 2013, for a total of more than 770, 000 marriages. The findings indicate that remarried couples are considerably more prone to divorce compared to couples married for the first time, particularly marriages in which both partners are remarried and marriages in which at least one of the partners is married for the third time or more. The differences between the various groups of marriages decline with a longer duration of the marriage.